News about VDAC1 in Hypoxia - Mazure, N. M. (Frontiers in Oncology, 2016)
The voltage-dependent anion channel (VDAC) is the main interface between the cytosol and mitochondria of cells. It plays a crucial role in both mitochondrial metabolism and cell death. The main basic function of this channel is to mediate and gate the flux of small ions, metabolites and ATP. Changes in its structure, and thus conformation, are expected to affect its activity and modulates the ability of cancer cells to expand. In this review, we describe a novel mechanism by which mitochondria of cells in hypoxia, a low level of oxygen, protects from apoptosis. In hypoxia some mitochondria become enlarged due to hyperfusion. These mitochondria possess a truncated form of VDAC1 (VDAC1-ΔC), which is linked to the higher metabolic capacity and the greater resistance to cell death of hypoxic cells. However, not all of the VDAC1 protein is truncated, but the amount of the full-length form is diminished compared to the amount in normoxic cells. First, we describe how such a decrease effects cell proliferation, respiration, glycolysis and other processes. Second we report on a novel mitochondrial-endolysosomal crosstalk that leads to VDAC1 truncation. By pharmacological targeting of VDAC1-ΔC, the production of energy could be turned off and the sensitivity to cell death restored. This could counteract the favorable microenvironment that gives cancer cells a growth advantage and thereby disrupts the balance between life and death, which is controlled by VDAC1.